500 years of Tantrasangraha : a landmark in the history of astronomy - Sriram, M. S.; Ramasubramanian, K.; Srinivas, M. D.; Indian Institute of Advanced Study. Inter-University Centre (Shimla : Inter-University Centre, Indian Institute of Advanced Study, 2002)
Study on Tantrasangraha, astronomical text by Kerala astronomer Nilakantha Somayaji, 1444-1545; contributed seminar articles.
Includes bibliographical references (p. [185]).
Includes passages in Sanskrit.
Keywords: Hindu astronomy